"I know it when I hear it": On listeners' perception of mistuning. (20th July 2018) - Larrouy-Maestri, Pauline
Listeners regularly judge the accuracy of musical performances. However, as is true for several types of judgments (e.g., beauty or obscenity), estimating the correctness of melodies is not based on a precise definition of the object/performance but rather follows arguments such as "I know it when I hear it". In order to clarify the definition of correctness in melodies, participants identified parametrically manipulated sung melodies as in-tune or out-of-tune, using the method of limits procedure (Experiment 1). Listeners' tolerance with regard to mistuning was compared across melodies (Experiment 2). The potential roots of correctness perception were investigated by testing the effect of familiarity, the influence of formal musical training (Experiment 3), and the task repetition effect (Experiment 4). The results highlight a surprisingly small tolerance with regard to mistuning (half of a quarter tone), whatever the melodic context, large individual differences, but high consistency over time. This high sensitivity was mainly modulated by musical training as well as by previous exposure. In addition to defining the boundary between in- and out-of-tune melodies, this study supports the implicit development of the normative notion of "correctness" as a category that might drive listeners' appreciation of artistic performances.